(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
Which one should be your priority?- This is a question that the majority of women still face whenever they decide to do something beyond their homes. Even after 54 years of Bangladesh’s independence, a large portion of the population still firmly holds onto socio-cultural norms and beliefs. This male-dominant society still believes that women’s first and only responsibility should be to take care of their families. However, people are now slowly realizing that women’s entrepreneurship can not only improve the family’s financial stability but also strengthen the country’s overall economy. Modern technologies are creating new opportunities for women to become successful entrepreneurs. However, they are still fighting for access to capital, overcoming social and religious norms, dealing with the pressure of family responsibilities, and lacking training and education, among other challenges, on their way to their dreams. This study analyzes the constraints and future prospects of women’s entrepreneurship in the digital age using the case study method. Developing policies that consider the proper use of modern technologies, the proper implementation of existing policies, easing capital management, eliminating socio-cultural hindrances, and ensuring stable political conditions are some of the significant ways to take women entrepreneurship to the next level, thereby increasing its contribution to national GDP.A